KUALITAS PENYUSUNAN RENCANA PEMBELAJARAN PADA SATUAN PENDIDIKAN TINGKAT ATAS - M. Nur Mustafa; Hermandra Hermandra; Zulhafizh Zulhafizh (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study was to describe and analyze the quality of learning planning among top-level teachers in Siak Regency, Riau Province. The research method used is descriptive qualitative to the research response instrument. The main sources of research are teachers in the upper-level education unit of Siak Regency, Riau Province, who opened 142 people. The data collection technique was using a Likert questionnaire. The instrument used is based on the provisions of the teacher and lecturer law. Data analysis through descriptive statistics. The research findings revealed that quality of making lesson plans of senior high school teachers in Siak regency belong to the very high category 4.304 or 86.10%. The lesson plans aimed to match teaching material with predetermined competencies, allocate time effectively and efficiently, decide media/ tools as well as teaching materials, describe learning objectives and in detail, decide assessment techniques in accordance with the demands of the curriculum, organize teaching materials based on sequences and groups, decide appropriate teaching methods, design learning procedures in accordance with competencies required, and decide appropriate references (textbooks, modules, computer program and so forth) to be used. These findings show that making a lesson plan requires creativity and pedagogical skills. Creativity and motivation lead to positive action in presenting quality, realistic, and concrete lesson plans.